0519 Sleep Dysfunction in Rett Syndrome. (25th May 2022) - Bricker, Katelyn; Vaughn, Bradley; Roth, Heidi; Walker, Nathan; Fan, Zheng (Jane)
Abstract: Introduction: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder affecting females and is linked to mutations in the methyl-CpG-binding protein 2 (MeCP2) gene. Typical comorbidities in RTT include poor growth, feeding difficulties, hyperventilation and breath-holding, seizures, scoliosis, and disrupted sleep. A few studies indicate sleep disruption in patients with RTT yet there is minimal data on polysomnographic findings in this population. We reviewed our cohort of Rett syndrome patients who underwent polysomnography. Methods: This retrospective case control of 10 RTT subjects (mean age, 11.19 years; ranged from 1 to 33 years) underwent standard polysomnography (PSG) recording. Subjects were compared to 10 age and gender matched controls with an AHI <5 and no chronic medical problems using a student paired t test. All studies were scored using the AASM criteria. Results: We found our cohort to have increased N3% sleep, decreased N2%, and shorter sleep onset latency (p< 0.05). Trends of lower BMI, lower oxygen saturation, and shorter REM latency (p < 0.10 but > 0.05). Review of PSGs shows the slow wave have morphological of typical slow waves and not that of the slowing seen on wake EEG nor the epileptiform activity. 4 of the 10 PSGs are notable for frequent interictal epileptiform discharges. 2 of the 10 subjects had a central apnea index >5, 2 had an AHI >5 and 1 demonstrated hypoventilation. There were central apneas associated with hyperventilation during awake and sleep-awake transition. Conclusion: Our cohort of RTT patients demonstrates differences in sleep architecture, manifested most notably by a high percentage of SWS. This population has high amplitude rhythmic slow (theta) activity on wake EEG, primarily in the frontal-central regions. This slowing was distinct from the epileptiform activity seen in 40% of our cohort. Central apnea also appeared in older patients and the very young. Larger population studies are needed for future research. Support (If Any):